トウキョウ ショウワ キチ カイセン ニオケル JJY10MHzハ ノ デンパン トクセイ - 杉内, 英敏; スギウチ, ヒデトシ; 山崎, 一郎; ヤマザキ, イチロウ; 城, 功; シロ, イサオ; 小宮, 紀旦; コミヤ, ノリアキ; SUGIUCHI, Hidetoshi; YAMAZAKI, Ichiro; SHIRO, Isao; KOMIYA, Noriaki (国立極地研究所, 1979)
P(論文) 昭和基地において,1974年1月から1975年12月までに測定されたJJY10MHz波の受信強度と,CCIRにより採択された電界強度の暫定計算法を基にした計算法による値との比較を行った.その結果,東京-昭和基地回線における受信強度の日変化は,計算による最高利用周波数が,受信周波数に比し十分高いときには計算値に合致するが,受信周波数と同等,またはそれ以下となる時間帯では大きな差が認められる.その原因の一つは,計算法で考慮されていないE_S層による伝搬モードが,F層衰退時の極域において特に有効となるためである.また,地表および電離層の不規則性によって生じる大円通路を外れた側方散乱波の存在,電離層反射時の吸収等に対する考慮が,計算に含まれていないことが原因として考えられる.本沢定によって,この回線では年間を通じほぼ一定の通信可能時間帯が期待てきることが判明した. The field strength of the standard frequency waves (JJY) at 10 MHz, measured at Syowa Station in Antarctica, for two years from January 1974 through December 1975 was compared with the value derived from the prediction method which is based on the CCIR Interim Method. According to the diurnal variation obtained, the predicted strength shows a good agreement with the measured values when the MUF of the circuit (Tokyo-Syowa) exceeds sufficiently the operating frequency. On the other hand, the predicted strength shows a large difference from the measured value when the MUF is comparable to or below the operating frequency. This discrepancy is considered to be caused partly by the E_s propaeation mode which is not taken into account in the prediction method. The examination is made in this paper for other anomalous propaeation mode such as the off-great circle path associated with the ground side-scatter, including the deviative absorption loss. The reception rate is also investigated statistically for the purpose of establishing Tokyo-Antarctica communication circuit. departmental bulletin paper